Research on Kinematic Characteristics of the Gear Rotating Guide-bar Mechanism Based on Differential of the Rotational Vector - Li Desheng; Wang Zhijun; Yu Jiangtao; Feng Yongli; Huang Baowang; Li Zhanxian (Jixie chuandong)
According to the principle of cycloid generation, the gear rotating guide bar mechanism is designed. The motion matrix equation of the mechanism is given by the method of rotation vector differentiation, and the influence of the number of cycloid lobes and the position of the rocker on the motion characteristics of the mechanism is studied. The results show that the lobe number of the hypocycloid only affects the rotating guide-bar on the angular velocity pulsation, but has little effect on the velocity pulsation. There will be two spike pulses on the angular velocity of the rotating guide-bar when the oscillating slider is located at the axisymmetric line on the sharp corner side, which however would be only one at other locations except center of the hypocycloid. The position of the rocking block only affects the phase angle of the planetary gear during uniform acceleration motion of the rotating guide rod, but it has no effect on the phase angle of the planetary gear during uniform deceleration motion.